2016
DOI: 10.3389/fmicb.2016.01572
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Involved in Indole-3-Acetic Acid Biosynthesis by Gluconacetobacter diazotrophicus PAL5 Strain Using Transposon Mutagenesis

Abstract: Gluconacetobacter diazotrophicus is a beneficial nitrogen-fixing endophyte found in association with sugarcane plants and other important crops. Beneficial effects of G. diazotrophicus on sugarcane growth and productivity have been attributed to biological nitrogen fixation process and production of phytohormones especially indole-3-acetic acid (IAA); however, information about the biosynthesis and function of IAA in G. diazotrophicus is still scarce. Therefore, the aim of this work was to identify genes and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 82 publications
2
14
0
1
Order By: Relevance
“…Pedraza [54] also found that in G. diazotrophicus, IAM is not always active. Also, the recent work by Rodrigues et al [55] demonstrated that G. diazotrophicus cultures supplemented with Trp produce IAA via the indole-3-pyruvic acid (IPyA) pathway (Trp → IPyA → indoleacetaldehyde (IAAld) → IAA); in this study, the involvement of an L-amino acid oxidase gene cluster in the biosynthesis of IAA was also shown. In H. seropedicae the difficult discrimination is similar to the case of Arthrobacter spp.…”
Section: Discussionsupporting
confidence: 58%
“…Pedraza [54] also found that in G. diazotrophicus, IAM is not always active. Also, the recent work by Rodrigues et al [55] demonstrated that G. diazotrophicus cultures supplemented with Trp produce IAA via the indole-3-pyruvic acid (IPyA) pathway (Trp → IPyA → indoleacetaldehyde (IAAld) → IAA); in this study, the involvement of an L-amino acid oxidase gene cluster in the biosynthesis of IAA was also shown. In H. seropedicae the difficult discrimination is similar to the case of Arthrobacter spp.…”
Section: Discussionsupporting
confidence: 58%
“…One of the main impacts of PGPB and HSs on plant growth is the improvement in the acquisition of nutrients and stimulation of the root system. Frequently, these effects are related to auxin or the "auxin-like effect" (Canellas et al, 2002;Zandonadi et al, 2007;Spaepen et al, 2014;Rodrigues et al, 2016). It has been proposed that the role of auxin in plant growth is related to the induction of (PM) H+-ATPase activity, which generates apoplastic acidification and thus provides loosening of the cell wall, allowing cell elongation (Hager et al, 1991;Frías et al, 1996).…”
Section: Humic Substances and Plant Growth-promoting Bacteria Improve Plant Growth Under Abiotic Stress Conditionsmentioning
confidence: 99%
“…We provide genetic evidence that supports IAA production by the model alga Chlamydomonas via an unexpected LAAO-mediated pathway, which has thus far been restricted to a single bacterial species (Rodrigues et al, 2016). This finding supports a new role for microbial LAAOs in auxin production that may be widespread in other algal lineages (Calatrava et al, 2019; Labeeuw et al, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…For these new applications, understanding how and under what environmental conditions IAA is produced by rhizospheric and phyllospheric algae is of great interest. Bacterial degradation of IAA has been shown to be essential for rhizosphere colonization and plant growth promotion (Zúñiga et al, 2013), and similar to how LAAO-mediated auxin production is involved in plant growth promotion by G. diazotrophicus (Rodrigues et al, 2016), auxin production by other LAAO-containing microbes in the rhizosphere like Chlamydomonas could have an impact on plant growth and fitness. Our findings suggest that future studies should carefully consider the role that terrestrial algae play in plant microbiomes (Lee and Ryu, 2021) and in the historical record of land plant evolution (Puginier et al, 2022).…”
Section: Discussionmentioning
confidence: 99%